Influencia de un programa de balonmano en la coordinación dinámica general de los estudiantes del grado 5° de la institución educativa Eudoro granada sede Agustín nieto de la ciudad de armenia. (2014)
Target: This study had as purpose, demonstrate the influence of a program of ball I flow in the dynamic coordination in the students of degree with 5 ° of the Educational Institution Eudoro Granada There sedates Agustín Nieto of the city of Armenia. Method: participation of 27 subjects between 9 and 13 years of age, proceeding from the Educational Institution Eudoro Granada There sedates Agustín Nieto of the city of Armenia. A pre realized test to evaluate at first the dynamic general coordination this way to apply the program and to determine the influence gathering final information with the pos test to realize the pertinent correlations. Results: the brave results decided in the test of Kolmogorov-Smirnov's normality, where it was possible to demonstrate that, the group control I present better results to statistical level, and the experimental one I do not present a significant improvement. Conclusions: According to the obtained results, the program of handball did not cause significant changes in the dynamic general coordination of the experimental group, but the classes of physical education that contain diversity of elements related to the motive development and that are realized by a minimal frequency of three times weekly, they contribute to the development of the dynamic general coordination in children from 9 to 13 years